Assimilation's agent : my life as a superintendent in the Indian boarding school system - Chalcraft, Edwin L., 1855-1943 (University of Nebraska Press, 2004)
Assimilation's Agent reveals the life and opinions of Edwin L. Chalcraft (1855-1943), a superintendent in the federal Indian boarding schools during the critical period of forced assimilation in the late nineteenth and early twentieth centuries. Chalcraft was hired by the Office of Indian Affairs (now known as the Bureau of Indian Affairs) in 1883. During his nearly four decades of service, he worked at a number of Indian boarding schools and agencies, including the Chehalis Indian School in Oakville, Washington; Puyallup Indian School in Tacoma, Washington; Chemawa Indian School in Salem, Oregon; Wind River Indian School in Wind River, Wyoming; Jones Male Academy in Hartshorne, Oklahoma; and Siletz Indian Agency in Oregon.